2021
DOI: 10.1051/e3sconf/202131601009
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Preference for Local Apples Malang and Imported Apples during the Pandemic

Abstract: Indonesian people tend to view imported fruit as a more prestigious value compared to local fruit. The case of pandemic covid19 has an impact on the imported fruit market in every country, especially apples that are famous in the Indonesian domestic market, among others, coming from China. People's fear of the transmission of covid19 brings its perception for consumers in consuming fruit originating from China. The purpose of this study is to know consumer preferences towards local Malang apples and imported a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…The findings have some implications, as follows: First, the availability of imported apples in the domestic market erodes the market of domestically grown apples, damaging the local economy and farmers’ incomes, as found by a study (Paxton, 2011). The previous study supports the massive availability of imported apples (Isaskar and Perwitasari, 2021). Data demonstrate that Indonesia underwent an increasing apple deficit (export minus import) from 2002 (US$ −68,312) to 2021 (US$ −374,148) (ITC Trade Map, 2023).…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…The findings have some implications, as follows: First, the availability of imported apples in the domestic market erodes the market of domestically grown apples, damaging the local economy and farmers’ incomes, as found by a study (Paxton, 2011). The previous study supports the massive availability of imported apples (Isaskar and Perwitasari, 2021). Data demonstrate that Indonesia underwent an increasing apple deficit (export minus import) from 2002 (US$ −68,312) to 2021 (US$ −374,148) (ITC Trade Map, 2023).…”
Section: Resultssupporting
confidence: 83%
“…The other study found that imported apples are preferred because of a factor of performance (size, colour, freshness, benefits, ease of obtaining, cleanliness and taste), packaging (packaging and label) and green product (organic) (Isaskar and Perwitasari, 2021). In the Indonesian context, domestic apples are mostly purchased by people with a range of monthly incomes between IDR 3 and 9m (around USD 192-575), falling into an indifferent and value-seeking cluster of consumers (Zamzami and Ariyawardana, 2019).…”
Section: Food Mile Problems Under Halal Supply Chainmentioning
confidence: 99%
See 3 more Smart Citations